2022
DOI: 10.1136/bmj-2021-068047
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of physical activity monitors in adults: systematic review and meta-analysis

Abstract: Objective To estimate the effectiveness of physical activity monitor (PAM) based interventions among adults and explore reasons for the heterogeneity. Design Systematic review and meta-analysis. Study selection The electronic databases MEDLINE, Embase, SPORTDiscus, CINAHL, and the Cochrane Central Register of Controlled Trials (CENTRAL) were searched on 4 June 2021. Eligible randomised controlled trials comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 174 publications
3
39
0
1
Order By: Relevance
“…Time spent sitting (sedentary time) is an independent risk factor for all cause mortality, cardiovascular disease, cancer, and type 2 diabetes 4. Kettle and colleagues reported no significant effect of primary care interventions on sedentary time, while Larsen and colleagues found that physical activity monitor based interventions were associated with a mean decrease of 9.9 min/day 79…”
Section: Broad Range Of Benefitsmentioning
confidence: 99%
See 2 more Smart Citations
“…Time spent sitting (sedentary time) is an independent risk factor for all cause mortality, cardiovascular disease, cancer, and type 2 diabetes 4. Kettle and colleagues reported no significant effect of primary care interventions on sedentary time, while Larsen and colleagues found that physical activity monitor based interventions were associated with a mean decrease of 9.9 min/day 79…”
Section: Broad Range Of Benefitsmentioning
confidence: 99%
“…Trials measuring physical activity with objective devices, such as accelerometers or wearable activity trackers, found no significant difference in MVPA between groups, while trials relying on self-reported activity showed an increase of 24 min/week in intervention groups 7. In a previous meta-analysis, Larsen and colleagues found that interventions using physical activity monitors increased MVPA by 48.5 min/week 9. But they judged this evidence to be ‘low certainty’ due to publication and small study biases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A week later, the CCM called the patient to discuss the current physical activity assessed by the accelerometer and gave advice on the preferred physical preoperative preparation. For example, patients were advised to train functional movements required after surgery, such as walking with a walking aid, or is advised to maintain or increase the current physical tness level by adhering to the World Health Organization's (WHO) latest physical activity guideline [13,25].…”
Section: Intervention: the Baas Clinical Pathwaymentioning
confidence: 99%
“…To enhance patients' participation in the BAAS clinical pathway, the patient, together with the physical therapist, sets realistic therapy goals using Goal Attainment Scaling, based on activities needed to RTW after surgery [12]. Also, a patient is equipped with an accelerometer before surgery until full RTW, which provides the patient and physical therapist insight in movement behavior and progression of activity levels during rehabilitation [13].…”
Section: Introductionmentioning
confidence: 99%